Evaluasi Program Kampung Iklim sebagai Upaya Pengelolaan Lingkungan Berkelanjutan di Kampung Airport Kecamatan Teluknaga Kabupaten Tangerang - Muhammad Miftah Farid; Juliannes Cadith (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Climate change is an urgent global challenge demanding local adaptation and mitigation. This research focuses on evaluating the sustainability of the Climate Village Program ProKlim in Kampung Airport, Teluknaga Village, Tangerang Regency. Although this location achieved national "ProKlim Utama" status in 2022, initial observations revealed a significant decline in program implementation. Identified issues include neglected facilities, suboptimal institutional management, decreased community participation, and regulatory gaps. This study employed a descriptive qualitative approach with a case study design, applying Leo Agustino’s policy evaluation model. Data was collected through interviews with relevant informants, direct field observations, and document analysis. The data analysis followed the interactive model of Miles and Huberman, with source and technique triangulation ensuring the findings' credibility. The research indicates that despite initial competence and positive characteristics of ProKlim managers, several factors hinder its sustainability. These include human resource capabilities technical skills and limited personnel, institutional management lack of formal structure and inconsistent monitoring, infrastructure maintenance damaged facilities and insufficient operational budget, and inadequate understanding of regulations. The long-term success of ProKlim in Kampung Airport is threatened by a lack of strong institutionalization, consistent resource allocation, and sustained multi-stakeholder involvement beyond the initial certification momentum.